Glass strengthening salt bath potassium additive and preparation method thereof

By adjusting the content of silica and aluminum trioxide, forming a stable structure and increasing pores, the existing glass reinforced salt bath potassium additives have been solved, and the efficient and environmentally friendly glass reinforcement effect is achieved.

CN119504153APending Publication Date: 2025-02-25CHANGSHA DAIHUA TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411678712.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-22
Publication Date
2025-02-25

AI Technical Summary

Technical Problem

The existing glass reinforced salt bath potassium additives have unstable structure at high temperatures, low absorption efficiency, and serious salt bath poisoning problems, which affects the glass reinforcement effect.

Method used

By adjusting the content of silica and aluminum trioxide, a stable structure is formed, suitable for high-temperature environments, and the specific surface area is increased by forming holes to improve absorption efficiency.

Benefits of technology

It achieves structural stability at high temperatures of 400℃ to 630℃, rapidly absorbs lithium ions, improves the glass reinforcement effect, reduces the risk of salt bath poisoning, and is environmentally friendly and pollution-free.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005147733830000061
    Figure BDA0005147733830000061
  • Figure BDA0005147733830000071
    Figure BDA0005147733830000071
  • Figure BDA0005147733830000081
    Figure BDA0005147733830000081
Patent Text Reader

Abstract

The invention provides a glass strengthening salt bath potassium additive which comprises the following components in percentage by mole based on oxides: 37-49% of sodium oxide and / or potassium oxide, 1-3% of calcium oxide, 30-40% of silicon dioxide and 15-25% of aluminum oxide, wherein the sum of the content of the silicon dioxide and the content of the aluminum oxide is larger than 50%. The content of silicon dioxide and the content of aluminum oxide are adjusted, so that the additive forms a stable structure, the additive can be suitable for high working temperature, and the absorption efficiency is improved. The method can be applied to purification of glass, glass ceramics, salt compounds containing impurity lithium ions and the like.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of glass strengthening, and more specifically, to a glass strengthening salt bath potassium treasure additive and a preparation method thereof. Background Art

[0002] Chemical strengthening of glass is to improve the strength of glass by changing the chemical composition of the surface, and is generally strengthened by ion exchange. The glass is immersed in a molten salt bath, so that the ions on the surface of the glass are exchanged with the ions in the salt bath, and an ion exchange layer is formed on the surface. The difference in the expansion coefficient of the ions is used, so that the outer layer shrinks less and the inner layer shrinks more during the cooling process. When cooled to room temperature, the glass is in a state where the inner layer is tensile and the outer layer is compressed, and strengthened glass is obtained. As the number of processed glasses increases, more ions are exchanged in the glass, which increases the concentration of glass ions in the salt bath, leading to salt bath poisoning, affecting the efficiency of ion exchange between the glass and the salt bath, and reducing the effect of glass strengthening. In addition, the working temperature of existing potassium additives for glass strengthening salt baths is usually around 400°C, and the absorption efficiency is not high. Summary of the invention

[0003] In order to solve the above-mentioned technical problems, the present invention provides a glass strengthening salt bath potassium treasure additive and its preparation method and application. By adjusting the content of silicon dioxide and aluminum oxide, the additive forms a stable structure, can be applied to higher working temperatures, and improves the absorption efficiency.

[0004] In order to achieve the above object, the technical solution of the present invention is as follows:

[0005] A glass strengthening salt bath potassium additive comprises the following components based on the molar percentage of oxides: 37% to 49% of sodium oxide and / or potassium oxide, 1% to 3% of calcium oxide, 30% to 40% of silicon dioxide, and 15% to 25% of aluminum oxide; wherein the sum of the content of silicon dioxide and aluminum oxide is greater than 50%.

[0006] In each component, the first metal oxide includes functional alkali metal oxides such as sodium oxide or potassium oxide. In the present invention, the source of potassium ions or sodium ions in the glass strengthening salt bath potassium treasure additive can also come from one or more of potassium hydroxide, potassium chloride, potassium nitrate, potassium silicate, and potassium oxide; or from one or more of sodium hydroxide, sodium chloride, sodium nitrate, sodium silicate, and sodium oxide. The raw materials can reduce costs and reduce the difficulty of melting.

[0007] The content of aluminum oxide is controlled at 15% to 25%, such as 15%, 16%, 17%, 18%, 19%, 20%, 21%, 22%, 24%, 25%, etc.; preferably greater than 15%. And the aluminum oxide / first metal oxide molar ratio is greater than 0.2. The higher the aluminum oxide content, the better the network structure and the faster the exchange rate of the glass strengthening salt bath potassium treasure additive, but too high alumina will make it difficult to form the glass strengthening salt bath potassium treasure additive.

[0008] Silicon dioxide is an essential component, used to form the skeleton of the network structure of the glass-strengthening salt bath potassium treasure additive with covalent bonds. The selection of its composition and content directly affects the adsorption performance of the network structure of the glass-strengthening salt bath potassium treasure additive. Its content is controlled at 30% to 40%; for example, 30%, 31%, 32%, 33%, 34%, 35%, 36%, 37%, 38%, 39%, 40%, etc.

[0009] The content of silicon dioxide + aluminum oxide is controlled to be greater than 50%. Silicon oxide and aluminum oxide are components of the network structure. The higher their content, the more stable the structure. Ensuring that the amount of network structure in the glass-strengthening salt bath potassium treasure additive is greater than 30% of the glass-strengthening salt bath potassium treasure additive is conducive to obtaining a stable glass-strengthening salt bath potassium treasure additive structure, which is more resistant to decomposition at high temperatures. The content of silicon dioxide + aluminum oxide can be 51%, 52%, 53%, 54%, 55%, 56%, 58%, 59%, 60%, 61%, 62%, 63%, 64% or 65%, etc.

[0010] The content of calcium oxide is controlled to be less than or equal to 3%. The main components of glass are silicon dioxide and sodium oxide, but sodium oxide increases the thermal expansion coefficient of glass and reduces the thermal stability, chemical stability and mechanical strength of glass, so the proportion cannot be introduced too much. In order to improve the chemical stability and mechanical strength of glass, it is necessary to introduce calcium ions with an ion radius similar to that of sodium ions but a divalent charge into the glass to increase the binding force between silicon dioxide chains. The main function of calcium oxide in glass is to increase the chemical stability and mechanical strength of glass, but when the content is high, it can increase the crystallization tendency of glass and make the glass brittle. The content of calcium oxide can be 1%, 1.1%, 1.2%, 1.3%, 1.5%, 1.8%, 2.0%, 2.2%, 2.4%, 2.5%, 2.7%, 2.8%, 2.9% or 3.0%, etc.

[0011] The present invention also provides a method for preparing the above-mentioned glass strengthening salt bath potassium treasure additive, comprising the following steps: mixing the components according to molar percentage, then melting them at 1000°C to 1500°C to form a liquid state, and forming them by any one of water quenching into particles, external force rolling or drawing into sheets, and foaming agent pore formation.

[0012] Further, the particles are formed by water quenching, wherein the water quenching temperature is 10°C to 80°C, such as 10°C, 15°C, 20°C, 22°C, 25°C, 30°C, 35°C, 45°C, 50°C, 60°C, 65°C, 70°C, 75°C or 80°C, etc., and the size of the glass strengthening salt bath potassium treasure additive particles is controlled by controlling the temperature, so that the glass strengthening salt bath potassium treasure additive particles meet 1mm to 10mm, such as 1mm, 1.5mm, 2mm, 2.5mm, 3mm, 4mm, 5mm, 6mm, 7mm, 8mm, 9mm or 10mm, etc. Preferably, it is between 2mm and 5mm.

[0013] Furthermore, the additive is rolled or drawn by external force into a sheet, and its thickness is 0.3 mm to 1 mm, for example, 0.3 mm, 0.4 mm, 0.5 mm, 0.6 mm, 0.7 mm, 0.8 mm, 0.9 mm or 1 mm, etc. Preferably, it is 0.4 mm to 0.6 mm. Its shape is an irregular sheet, and its shortest side is at least 0.3 cm, and its largest side is less than 1 cm.

[0014] Furthermore, a porous fragment-shaped additive can be made by adding a foaming agent, and the pore size can be adjusted by adjusting the proportion of the foaming agent, and the pore size is 1mm to 10mm; for example, 1mm, 2mm, 3mm, 4mm, 5mm, 6mm, 7mm, 8mm, 9mm or 10mm. The shortest side of the diameter of the fragment is at least 0.5cm, and the longest side is less than 10cm. The foaming agent is a conventional foaming agent in the art, and is not limited to increase the specific surface area of ​​the additive. The glass salt bath strengthening additive obtained by the above method has uniform pores on its surface for absorbing impurity ions in the molten salt.

[0015] Furthermore, the present invention also discloses the application of the above-mentioned glass strengthening salt bath potassium treasure additive, which can be applied to the strengthening of glass and microcrystalline glass, and is also widely applicable to the purification of degraded salt compounds or salt compounds containing impurities such as lithium ions.

[0016] Compared with the prior art, the advantages of the present invention are:

[0017] 1. The glass strengthening salt bath potassium treasure additive provided by the present invention selects specific contents of silicon dioxide and aluminum oxide to form polar covalent bonds and ionic bonds, and sets specific contents of sodium oxide / potassium to melt and foam at high temperature to form holes to increase the specific surface area and improve the adsorption amount of smaller metal cations; and forms lattice gaps to improve the adsorption rate of smaller metal cations. The holes formed on its surface are used to absorb impurity ions in the molten salt, so that the final glass strengthening salt bath potassium treasure additive material has excellent adsorption performance for lithium ions, will not introduce other impurity ions into the molten salt compound, and effectively and directionally remove metal impurity ions in the molten salt compound; and the additive after use will not pollute the environment; more importantly, the structure of the glass strengthening salt bath potassium treasure additive is stable.

[0018] 2. The glass strengthening salt bath potassium treasure additive provided by the present invention has a stable structure at high temperatures of 400°C to 630°C, can absorb lithium ions continuously and quickly at high temperatures, and does not increase operating costs; it is particularly targeted at the absorption of poisoning ions lithium (salt bath poisoning: salt bath poisoning refers to the gradual increase of smaller alkali metal cations in the glass during the ion exchange process beyond the threshold limit, and the smaller alkali metal cations in the invention are lithium ions, so it is understood as lithium ion poisoning), and has the characteristics of high absorption rate and controllable absorption rate; it quickly absorbs lithium ions and sodium ions generated in the molten salt during the chemical strengthening of glass through ion screening, ensuring that the concentrations of lithium ions and sodium ions in the molten salt are within a stable range, ensuring the stability of the mass production size of chemically strengthened glass and the stability of surface stress; it can quickly exert the absorption effect, and can be easily and quickly removed to avoid reducing production efficiency.

[0019] 3. The preparation method provided by the present invention has diversified and controllable production processes. By selecting different molding methods, it can be made into 1mm to 10mm granular, irregularly shaped and 0.3mm to 1mm thick sheets or 1mm to 10mm porous glass-reinforced salt bath potassium treasure additives. Glass-reinforced salt bath potassium treasure additives of different forms are obtained, and holes for increasing the absorption area of ​​the glass-reinforced salt bath potassium treasure additives are formed on the surface of the glass-reinforced salt bath potassium treasure additives to improve the absorption efficiency.

[0020] 4. The glass strengthening salt bath potassium treasure additive provided by the present invention has a wide range of applications. It can not only be used in the field of glass and microcrystalline glass ion exchange, so that glass and microcrystalline glass can normally perform ion exchange in ultra-high temperature molten salt, but also is widely applicable to the purification of degraded molten salt or molten salt containing impurities such as lithium ions. The glass strengthening salt bath potassium treasure additive provided by the present invention can improve production efficiency, reduce production costs, and is environmentally friendly and pollution-free. DETAILED DESCRIPTION

[0021] In order to facilitate the understanding of the present invention, the present invention will be described more comprehensively and meticulously in combination with preferred embodiments below, but the protection scope of the present invention is not limited to the following specific embodiments.

[0022] Unless otherwise defined, all professional terms used below have the same meanings as those generally understood by those skilled in the art. The professional terms used herein are only for the purpose of describing specific embodiments and are not intended to limit the scope of protection of the present invention.

[0023] Unless otherwise specified, various raw materials, reagents, instruments and equipment used in the present invention can be purchased from the market or prepared by existing methods.

[0024] Examples 1-5 and Comparative Examples 1-7

[0025] A glass strengthening salt bath potassium additive, based on the molar percentage of oxides, has component contents as shown in Table 1.

[0026] Table 1 Component contents of glass strengthening salt bath potassium treasure additives (based on the total molar amount of oxides as 100%)

[0027]

[0028] The raw materials are prepared according to the component contents in Table 1, and then smelted at 1000°C to 1500°C to form a liquid state, and then formed by any one of water quenching into particles, external force rolling or drawing into sheets, and foaming agent pore formation to obtain a glass-reinforced salt bath potassium treasure additive.

[0029] The additives obtained by the above-mentioned embodiments and comparative examples are used for strengthening microcrystalline glass. The added amount is about 3wt% of the mass of the molten salt, the temperature is 400℃~630℃, and the strengthening time is 4-24h. The measurement results before and after strengthening are compared and analyzed. The atomic absorption spectrophotometer is used to measure the lithium ion content in the molten salt after the addition of the additives. The results are shown in Table 2.

[0030] Table 2

[0031]

[0032]

[0033] As shown in Table 2, the additive obtained in the embodiment has a high absorption rate and high efficiency, and is suitable for working environments exceeding 600°C, meeting the strengthening requirements of microcrystalline glass and the like. In Comparative Example 1, the amount of sodium chloride used is less than 37%, and the absorption effect of lithium ions is not good. In Comparative Example 2, the total content of silicon dioxide and aluminum oxide is less than 50%, and strengthening is performed at 550°C. Although the lithium ion content is less than 16ppm, the structure of the additive is unstable, causing erosion on the glass surface.

[0034] In Comparative Examples 3-5, zirconium oxide, zinc oxide, and magnesium oxide are used to replace calcium oxide. Although the obtained additives meet the requirements for lithium ion content in microcrystalline glass, they have poor high temperature stability and are easy to corrode the glass, affecting the quality of microcrystalline glass products. In Comparative Example 6, the calcium oxide content is relatively high, resulting in white spots on the microcrystalline glass, affecting the product quality. In Comparative Example 7, no calcium oxide is added, and the obtained additive structure is unstable, causing corrosion to the glass surface.

[0035] The above-mentioned embodiments only express several implementation methods of the present invention, and the descriptions thereof are relatively specific and detailed, but they cannot be understood as limiting the scope of the invention patent. It should be pointed out that, for ordinary technicians in this field, several variations and improvements can be made without departing from the concept of the present invention, and these all belong to the protection scope of the present invention. Therefore, the protection scope of the patent of the present invention shall be subject to the attached claims.

Claims

1. A glass strengthening salt bath potassium treasure additive, characterized in that: Based on the molar percentage of oxides, the composition includes: 37% to 49% sodium oxide and / or potassium oxide, 1% to 3% calcium oxide, 30% to 40% silicon dioxide, and 15% to 25% aluminum oxide; wherein the sum of the content of silicon dioxide and aluminum oxide is greater than 50%.

2. The glass strengthening salt bath potassium treasure additive according to claim 1, characterized in that: The potassium oxide is one or more of potassium hydroxide, potassium chloride, potassium nitrate, potassium silicate and potassium oxide.

3. The glass strengthening salt bath potassium treasure additive according to claim 1, characterized in that: The sodium oxide is one or more of sodium hydroxide, sodium chloride, sodium nitrate, sodium silicate and sodium oxide.

4. The method for preparing the glass strengthening salt bath potassium treasure additive according to any one of claims 1 to 3, characterized in that: The method comprises the following steps: dispensing the components according to molar percentage, then melting them at 1000-1500°C to form a liquid state, and then forming the liquid by water quenching into particles, external force rolling or drawing into sheets, or foaming agent forming holes.

5. The method for preparing the glass strengthening salt bath potassium treasure additive according to claim 4, characterized in that: The water quenching temperature is 10°C to 80°C, and the particle size of the particles is 1mm to 10mm.

6. The method for preparing the glass strengthening salt bath potassium treasure additive according to claim 5, characterized in that: The particle size of the particles is 2 mm to 5 mm.

7. The method for preparing the glass strengthening salt bath potassium treasure additive according to claim 4, characterized in that: The sheet is in an irregular sheet shape, with the shortest side being at least 0.3 cm and the longest side being less than 1 cm; the thickness of the sheet is 0.3 mm to 1 mm.

8. The method for preparing the glass strengthening salt bath potassium treasure additive according to claim 7, characterized in that: The thickness of the sheet is 0.4 mm to 0.6 mm.

9. The method for preparing the glass strengthening salt bath potassium treasure additive according to claim 4, characterized in that: The additive formed by forming pores through a foaming agent is in the form of porous fragments, the shortest side of which is at least 0.5 cm in diameter and the longest side is less than 10 cm; the pore diameter is 1 mm to 10 mm.